C-type natriuretic peptide ameliorates pulmonary fibrosis by acting on lung fibroblasts in mice. Issue 1 (December 2016) - Kimura, Toru; Nojiri, Takashi; Hino, Jun; Hosoda, Hiroshi; Miura, Koichi; Shintani, Yasushi; Inoue, Masayoshi; Zenitani, Masahiro; Takabatake, Hiroyuki; Miyazato, Mikiya; Okumura, Meinoshin; Kangawa, Kenji
Abstract Background Pulmonary fibrosis has high rates of mortality and morbidity; however, no effective pharmacological therapy has been established. C-type natriuretic peptide (CNP), a member of the natriuretic peptide family, selectively binds to the transmembrane guanylyl cyclase (GC)-B receptor and exerts anti-inflammatory and anti-fibrotic effects in various organs through vascular endothelial cells and fibroblasts that have a cell-surface GC-B receptor. Given the pathophysiological importance of fibroblast activation in pulmonary fibrosis, we hypothesized that the anti-fibrotic and anti-inflammatory effects of exogenous CNP against bleomycin (BLM)-induced pulmonary fibrosis were exerted in part by the effect of CNP on pulmonary fibroblasts. Methods C57BL/6 mice were divided into two groups, CNP-treated (2.5 μg/kg/min) and vehicle, to evaluate BLM-induced (1 mg/kg) pulmonary fibrosis and inflammation. A periostin-CNP transgenic mouse model exhibiting CNP overexpression in fibroblasts was generated and examined for the anti-inflammatory and anti-fibrotic effects of CNP via fibroblasts in vivo. Additionally, we assessed CNP attenuation of TGF-β-induced differentiation into myofibroblasts by using immortalized human lung fibroblasts stably expressing GC-B receptors. Furthermore, to investigate whether CNP acts on human lung fibroblasts in a clinical setting, we obtained primary-cultured fibroblasts from surgically resected lungs of patients with lung cancer and analyzed levels of GC-B mRNA transcription. Results CNP reduced mRNA levels of the profibrotic cytokines interleukin (IL)-1β and IL-6, as well as collagen deposition and the fibrotic area in lungs of mice with bleomycin-induced pulmonary fibrosis. Furthermore, similar CNP effects were observed in transgenic mice exhibiting fibroblast-specific CNP overexpression. In cultured-lung fibroblasts, CNP treatment attenuated TGF-β–induced phosphorylation of Smad2 and increased mRNA and protein expression of α-smooth muscle actin and SM22α, indicating that CNP suppresses fibroblast differentiation into myofibroblasts. Furthermore, human lung fibroblasts from patients with or without interstitial lung disease substantially expressed GC-B receptor mRNA. Conclusions These data suggest that CNP ameliorates bleomycin-induced pulmonary fibrosis by suppressing TGF-β signaling and myofibroblastic differentiation in lung fibroblasts. Therefore, we propose consideration of CNP for clinical application to pulmonary fibrosis treatment.